2012
DOI: 10.1371/journal.pone.0034093
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 Modulates Intracellular Growth of Salmonella Pathogenicity Island 2 Mutants and Production of Cytokines in Infected Monocytic U937 Cells

Abstract: Background Salmonella enterica serovar Enteritidis PT4 KS8822/88 replicates rapidly in HLA-B27-transfected human monocytic U937 cells. In this process, Salmonella pathogenicity island 2 (SPI-2) genes play a crucial role. Our previous study indicated that 118 Salmonella genes, including 8 SPI-2 genes were affected by HLA-B27 antigen during Salmonella infection of U937 cells. Methods/Princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 47 publications
0
11
0
2
Order By: Relevance
“…Evidence exists suggesting that the interaction between ReA-triggering bacteria and HLA-B27 expressing host cell is abnormal [2], [4], [8], [26], [27], [38], [39]. We have previously observed that the presence of HLA-B27 HCs in monocytic cells modifies intracellular environment of U937 monocyte/macrophages in favor of the disease-triggering bacteria and we found that the regulation of several signaling molecules was altered in these cells [1][3], [26].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Evidence exists suggesting that the interaction between ReA-triggering bacteria and HLA-B27 expressing host cell is abnormal [2], [4], [8], [26], [27], [38], [39]. We have previously observed that the presence of HLA-B27 HCs in monocytic cells modifies intracellular environment of U937 monocyte/macrophages in favor of the disease-triggering bacteria and we found that the regulation of several signaling molecules was altered in these cells [1][3], [26].…”
Section: Discussionmentioning
confidence: 63%
“…lipopolysaccharide (LPS) are shown to persist in ReA patients for an abnormally long time [4][7]. In fact, it is suggested that Salmonella is able to regulate its intracellular growth in the HLA-B27-positive cells and that might be a strategy for bacterial persistence [8]. Thus these observations suggest that the interaction between HLA-B27-expressing host cells and ReA-triggering bacteria is abnormal and leads to the persistence of the causative microbes/microbial compartments in ReA patients and to prolonged immune reaction.…”
Section: Introductionmentioning
confidence: 99%
“…HLA-B27 has multiple alleles that may affect the host response and disease susceptibility; among these, HLA-B*2703 increases the risk of the typical clinical triad of ReA [19]. Other data suggest that HLA-B27 may contribute to the persistence of bacteria in the host, especially Chlamydia and Salmonella [20,21]. So how does the susceptible HLA-B27 gene participate in the occurrence and development of ReA?…”
Section: Pathogenesis Of Reamentioning
confidence: 99%
“…For example, Granfors and colleagues have studied a monocyte cell line transfected with HLA B27 [20]. The presence of HLA B27 appears to affect the intracellular longevity of Salmonella .…”
Section: Links Between Bacteria and Spamentioning
confidence: 99%